International Economic Relations and World Economy - Balak, Ilona O. (My University, 2023)
The academic component "International Economic Relations and World Economy" studies and explains the basic processes and phenomena of economic life of the world community, covers the question of functioning of international cooperation between the different states at the present stage of the development. An important place in the course structure is the analysis of historical preconditions, structural parts of state economy, peculiarities of trade and economic cooperation between countries. The publication outlines the thematic structure of the lecture materialі, presents questions for seminar classes and test tasks for self-assessment, and a list of recommended references. It is recommended for students of 2 nd year for the bachelor’s degree preparation, specialty 291 «International Relations, Public Communication and Regional Studies», educational and professional program «International Relations»
Keywords: international economic relations; international relations; world economy; 339.9=111